If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 1 = 2x + 13 Reorder the terms: 1 + -10x = 2x + 13 Reorder the terms: 1 + -10x = 13 + 2x Solving 1 + -10x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + -10x + -2x = 13 + 2x + -2x Combine like terms: -10x + -2x = -12x 1 + -12x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + -12x = 13 + 0 1 + -12x = 13 Add '-1' to each side of the equation. 1 + -1 + -12x = 13 + -1 Combine like terms: 1 + -1 = 0 0 + -12x = 13 + -1 -12x = 13 + -1 Combine like terms: 13 + -1 = 12 -12x = 12 Divide each side by '-12'. x = -1 Simplifying x = -1
| -5x+-14=8 | | 85s-25=3 | | 1+x/3=-1 | | 16-8x=-48 | | x=0.8x+772 | | 9m+5n-4m+7n= | | 2223c=-535 | | 85s+25=3 | | 8n+1=73 | | 4xd+y-2dx=1 | | 3(7x+8)+6(4x+9)=21 | | 6=10+v/4 | | 2(w-3)-6w=34 | | -7+4r=-23 | | 24-4x=6(3-x) | | 7x+8=2x-2 | | 6x^2-34+20=0 | | 13x-17y=75 | | y=(x-6)m | | -5x+14=8 | | 222/3c=-53/5 | | 9x+6=4x-4 | | .3*4+x=.8(x+4) | | 180=90+x+90+30 | | 4(2t+5)=4t+10 | | 25b+what=30b | | -3y+6x=6 | | -10-9(x+9)= | | 3x^2-1x-30=30 | | 10x-3=35x-2 | | 6y+7x=1 | | 2x+40=x+73 |